Synergy of Sekura Local Wisdom in History Learning at Universitas Lampung - Ulul Azmi Muhammad; Een Yayah Haenilah; Risma Margaretha; Muhammad Fuad (Universitas Negeri Malang, 2025)
This study aims to examine the role of the Sekura tradition as a form of local wisdom of the Lampung community in supporting history learning in higher education, particularly at Universitas Lampung. Sekura, which is a cultural tradition with social, moral, and historical values, is seen as having potential as a contextual learning resource and is relevant to a local wisdom-based learning approach. The research method uses a qualitative approach with data collection techniques through literature studies, interviews with lecturers and students, and observations of Sekura cultural practices. The results show that the integration of Sekura in history learning can improve students' understanding of local cultural dynamics, strengthen regional identity, and encourage an appreciative attitude towards the plurality of Indonesian cultures. In addition, the application of this local wisdom supports the achievement of learning outcomes that emphasize critical, reflective, and contextual thinking skills. Thus, the synergy between Sekura and history learning not only preserves Lampung's cultural heritage but also enriches pedagogical strategies in history education at the university level.